Comparison of two types of biomecanics for deep overbite correction - Ana de Lourdes Sá de Lira; Yarasmin Nolêto de Sousa Alexandrino (Universidade Estadual de Campinas, 2015)
Aim: To compare two types of treatment for Class II deep overbite malocclusion assessing maxillary and mandibular arches behavior in subjects submitted to full orthodontic treatment with standard edgewise appliance and those who used straight wire appliance. Methods: The sample consisted of 50 patients treated with full fixed appliances either with edgewise appliance (n=25, Group 1), or with straight wire appliance (n=25, Group 2). In both groups lateral cephalometric radiographs were compared with those done at the beginning of treatment and at its end, in order to quantify the cephalometric measures (8 linear and 6 angular) presenting the maxillary and mandibular arches behavior in the anteroposterior and vertical directions. All patients were treated without extraction or use of Class II intermaxillary elastics during the full orthodontic treatment. Results: In both groups the treatment of malocclusion contributed for mandibular forward displacement, reduction of deep overbite and overjet, reduction of mandibular plane with anti-clockwise rotation and labial projection of maxillary incisors. Conclusions: In both groups the sample showed favorable mandibular displacement, reduction of facial convexity, and profile improvement with anti-clockwise rotation. The correction of deep overbite was due to labial projection and intrusion of maxillary incisors.